2011
DOI: 10.1002/app.29690
|View full text |Cite
|
Sign up to set email alerts
|

Measuring of coalescence in polymer melt blends flowing through converging channels

Abstract: Droplets of polymer blends flowing through convergent channels undergo collisions and coalescence because of the appropriate wineglass-shaped flow paths with essential flow constriction at the entrance zone. Therefore, an attempt has been undertaken to use capillary flow for studying coalescence phenomena in polymer blends. When the initial drop diameters in a barrel (before extrusion), d b , and in the extrudate, d e , are measured, coalescence efficiency can be easily calculated as E c ¼ de , provided that n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Shear flows have been proven to be less energy-efficient towards both dispersive and distributive mixing when compared to elongational flows [ 6 , 7 , 8 , 9 ]. Much effort has been devoted to developing plasticizing and conveying devices that impart elongation-dominated flows, such as the introduction of extensional mixing elements (EME) into the conventional single-screw [ 10 , 11 ] and twin-screw extruders [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shear flows have been proven to be less energy-efficient towards both dispersive and distributive mixing when compared to elongational flows [ 6 , 7 , 8 , 9 ]. Much effort has been devoted to developing plasticizing and conveying devices that impart elongation-dominated flows, such as the introduction of extensional mixing elements (EME) into the conventional single-screw [ 10 , 11 ] and twin-screw extruders [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there still exist some deficiencies like incomplete dispersion and distribution of primary CF agglomerates or the insufficient adhesion between CFs and the polymer matrix. It is testified that the dispersing efficiency under the extensional deformation is twice that under shear deformation when the deformation rate is equal [23,24]. To generate elongation flow and enhance the mixing efficiency, some novel mixing methods and corresponding devices such as vane extruder (VE) [25,26], vane mixer (VM) [27] were proposed.…”
Section: Introductionmentioning
confidence: 99%
“…These physical processing methods improved the thermal conductivity of composites to some extent, but they cannot avoid thermal degradation and shear degradation caused by the high local shear stress, which often weakens the composites' mechanical properties. However, it is well recognized that the mixing process dominated by extensional deformation has many advantages such as better dispersive and distributive mixing, reduced melt temperature, and wide adaptability . It is indicated that the dispersing and mixing efficiency under the extensional flow was 10 times higher than that under the shear flow if the deformation rate is equal .…”
Section: Introductionmentioning
confidence: 99%